Tiktok Herd: A Significance Study in the Tourism Industry - Belza, Alexandra Yvhonne M.; Del Rosario, Jeremiah Simon R.; Fowler, Alvine Roz B.; Lauron, Francelline M.; Lumabas, Aj Fares P.; Dellova, Rovena (LACULTOUR: Journal of Language and Cultural Tourism, 2024)
Many social media applications were established that increased tourists' dependability on social media for their travel decisions. However, one application led the Herd to bring the tourism industry back to its pedestal-the TikTok application. This descriptive research with a quantitative approach utilized snowball sampling with 400 TikTok users as respondents. The findings revealed that the TikTok application was a helpful platform for tourism destinations for either gaining information or affecting and helping with their travel decisions. Likewise, this application is an effective means to promote the Philippines' tourism industry and reach larger audiences. It influenced them to travel. Also, it is well known for its engaging and addictive nature because of its tailored feeds of amusing videos paired with music and sound effects. The analysis explores the reasons and social explanations for tourists' interaction with travel videos on the short-form video-sharing platform TikTok to comprehend how involvement with the TikTok application affects the tourism sector. However, the TikTok application positively impacts the tourism industry. It allows the users to be knowledgeable about tourism information, and it also showcases the tourism destination in the comfort of their homes through the screen of their mobile phones. Thus, the TikTok application is a powerful marketing tool, making it an excellent platform for attracting new tourists.